2003
DOI: 10.2337/diabetes.52.1.214
|View full text |Cite
|
Sign up to set email alerts
|

Variation in Resistin Gene Promoter Not Associated With Polycystic Ovary Syndrome

Abstract: Polycystic ovary syndrome (PCOS) is a leading cause of anovulatory infertility and affects ϳ4 -7% of reproductive age women in the U.S. It is characterized by hyperandrogenemia and chronic anovulation and is associated with insulin resistance, obesity, and increased risk for type 2 diabetes. In a screen of candidate genes, a region on chromosome 19p13.3 was identified that shows significant evidence for both linkage and association with PCOS. A promising candidate gene for PCOS, resistin, maps to exactly this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
1
4

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 22 publications
6
40
1
4
Order By: Relevance
“…In their study, no association of serum resistin levels with body mass index was observed. Variation in resistin gene promoter was not associated with PCOS (Urbanek et al, 2003). These findings suggest that resistin is unlikely to be a major determining factor in PCOS.…”
Section: Introductionsupporting
confidence: 46%
See 1 more Smart Citation
“…In their study, no association of serum resistin levels with body mass index was observed. Variation in resistin gene promoter was not associated with PCOS (Urbanek et al, 2003). These findings suggest that resistin is unlikely to be a major determining factor in PCOS.…”
Section: Introductionsupporting
confidence: 46%
“…The role of resistin in PCOS had been investigated in several studies, which proved that variation in resistin gene promoter was not associated with polycystic ovary syndrome (Urbanek et al, 2003). Serum resistin levels were not elevated in PCOS women with insulin resistance Seow et al, 2004), and resistin was therefore not regarded as a major determining factor of PCOS-associated insulin resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The SNPs had an allele frequency of >0.1 in Caucasians, and comprised four of the six common (>0.1) variations identified in previous studies that screened both coding and regulatory regions of the gene for polymorphisms [13,14,15,17,18,20,21]. In order to identify any additional SNPs in coding regions, we screened 760 bp of the promoter region and all four exons in 94 individuals of Finnish origin; however, we found no additional variants with an allele frequency of >0.1 [22]. The SNPs were genotyped by homogeneous MassEXTEND reaction using the MassARRAY System (Sequenom, San Diego, Calif., USA) as previously described [25].…”
Section: Methodsmentioning
confidence: 99%
“…This might also serve to increase our knowledge about certain forms of diabetes mellitus. For example, the chromosomal localization of the PTBP1 gene has been assigned to 19p13.3, which is a locus closely linked to Type 2 diabetes associated with the polycystic ovary syndrome (Urbanek et al, 2003). Furthermore, a model for increased insulin secretion in vivo displays signs of increased PTB binding to messengers for insulin and other secretory granule proteins (Kuwahata et al, 2007).…”
Section: Future Perspectivesmentioning
confidence: 99%